Effect of clay content on the morphological, thermo-mechanical and chemical resistance properties of propionic anhydride treated jute fiber/polyethylene/nanoclay nanocomposites - Rahman, M.R. (Elsevier, 2016)
Nanoclay is considered potential nanofiller for the manufacturing of natural fiber nanocomposites. The hydrophilic nature of natural fibers affects negatively its adhesion to hydrophobic polymer matrix. In the present study, propionic anhydride (PA) treated jute were used for the manufacturing of jute/polyethylene/nanoclay nanocomposites. Different amount (wt%) of montmorillonite (MMT) were used as nanofiller in order to optimize the nanoclay in the composite system. Finally, the nanocomposites were prepared using hot press machine at 5, 10, 15, and 20 wt% fiber loadings. Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), tensile tests, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and chemical resistance test were used to evaluate the morphological, thermo-mechanical and chemical resistance properties of the composites